Extractivism and Management of Vines in a Quilombola Community in the Brazilian Semiarid region (FLOVET - Boletim do Grupo de Pesquisa da Flora, Vegetação e Etnobotânica, 2025)
This study investigated the management and conservation of lianas in a quilombola community in Coração de Maria, Bahia. Interviews were conducted with 33 extractivists/artisans, along with field observations and botanical collections identified at UEFS. A total of 40 taxa from 12 families were identified, with Bignoniaceae being the most cited (64.68% of use mentions). Participants demonstrated extensive traditional knowledge, with women predominantly leading the activities, which are carried out without formal division of labor. Liana use is guided by traditional practices, but the analysis of harvest frequency showed no correlation between perceived abundance and use, suggesting potentially predatory management. As a result, it is recommended to develop sustainable management policies, conduct phytosociological and phenological studies, and promote the preservation and transmission of traditional knowledge, especially among younger generations, to ensure sustainable continuity of this activity.